Do ‘thinly-traded’ stocks benefit from specialist intervention? - Nimalendran, M.; Petrella, Giovanni (Journal of Banking & Finance, 2003)
This paper addresses the issue of the optimal trading system for less actively traded (i.e., ‘thinly-traded’) stocks. We compare the performance of a pure order driven market with limit order book (POD) with that of a hybrid order driven market with specialist and limit order book (HOD). We find that the HOD system offers superior performance along several dimensions of market quality. In particular, the specialist-based system offers lower execution costs, greater depth, a significant increase in the depth-to-spread ratio, and lower adverse selection costs. Very ‘thinly-traded’ stocks benefit more than less inactive stocks from the adoption of a hybrid trading system both in terms of greater liquidity and in terms of lower adverse selection costs.